Analisa Integrated Marketing Communication Melalui Event Marketing BNI Media Clash 3.0 KUY! Entertainment - Wicaksono, Primantyo Lebdho (Jurnal Manajemen dan Bisnis Madani, 2024)
its presence, KUY! Entertainment achieved very fast subscriber growth, but now the subscriber growth rate is decreasing. Therefore, an Integrated Marketing Communication was carried out through the BNI Media Clash 3.0 marketing event, to increase subscriber growth on the KUY! Entertainment YouTube channel. This research aims to analyze the implementation of Integrated Marketing Communication through the BNI Media Clash 3.0 marketing event and its impact on the KUY! Entertainment YouTube channel. This research uses a qualitative descriptive research method using semi-structured interviews conducted with several sources from KUY! Media Group consisting of Chief Marketing Officer, Head of Media Network, Head of Sales, Event Production Manager, and Creative Supervisor with triangulated sources from the Chairman of KUY! Media Group. According to the analysis of the implementation of integrated marketing communications through the BNI Media Clash 3.0 marketing event, KUY! Media Group has successfully completed all stages of Integrated Marketing Communication. Keywords: YouTube channel, marketing event, subscribers growth, integrated marketing communication